Involvement of arginine-specific cysteine proteinase (Arg-gingipain) in fimbriation of Porphyromonas gingivalis. - Nakayama, K (1996)
Arginine-specific cysteine proteinase (Arg-gingipain [RGP], a major proteinase secreted from the oral anaerobic bacterium Porphyromonas gingivalis, is encoded by two separate genes (rgpA and rgpB) on the P. gingivalis chromosome and widely implicated as an important virulence factor in the pathogenesis of periodontal disease (K. Nakayama, T. Kadowaki, K. Okamoto, and K. Yamamoto, J. Biol. Chem. 270:23619-23626, 1995). In this study, we investigated the role of RGP in the formation of P. gingivalis fimbriae which are thought to mediate adhesion of the organism to the oral surface by use of the rgp mutants. Electron microscopic observation revealed that the rgpA rgpB double (RGP-null) mutant possessed very few fimbriae on the cell surface, whereas the number of fimbriae of the rgpA or rgpB mutant was similar to that of the wild-type parent strain. The rgpB+ revertants that were isolated from the double mutant and recovered 20 to 40% of RGP activity of the wild-type parent possessed as many fimbriae as the wild-type parent, indicating that RGP significantly contributes to the fimbriation of P. gingivalis as well as to the degradation of various host proteins, disturbance of host defense mechanisms, and hemagglutination. Immunoblot analysis of cell extracts of these mutants with antifimbrilin antiserum revealed that the rgpA rgpB double mutant produced small amounts of two immunoreactive proteins with molecular masses of 45 and 43 kDa, corresponding to those of the precursor and mature forms of fimbrilin, respectively. The result suggests that RGP may function as a processing proteinase for fimbrilin maturation. In addition, a precursor form of the 75-kDa protein, one of the major outer membrane proteins of P. gingivalis, was accumulated in the rgpA rgpB double mutant but not in the single mutants and the revertants, suggesting an extensive role for RGP in the maturation of some of the cell surface proteins.